Membrane lipid changes in Arabidopsis thaliana in response to environmental stresses - Vu, Hieu Sy (Kansas State University, 2014)
The molecular mechanisms by which plants respond to environmental stresses to sustain growth and yield have great importance to agriculture. Lipid metabolites are a major element of plant stress responses. The model plant Arabidopsis thaliana is well-suited to study stress-driven compositional dynamics, metabolism, and functions of lipid metabolites. When Arabidopsis plants were subjected to wounding, infection by Pseudomonas syringae pv tomato DC3000 expressing AvrRpt2 (PstAvr), infection by Pseudomonas syringae pv. maculicola (Psm), and low temperature, and 86 oxidized and acylated lipids were analyzed using mass spectrometry, different sets of lipids were found to change in level in response to the various stresses. Analysis of plant species (wheat versus Arabidopsis), ecotypes (Arabidopsis Columbia 0 versus Arabidopsis C24), and stresses (wounding, bacterial infection, and freezing) showed that acylated monogalactosyldiacylglycerol was a major and diverse lipid class that differed in acyl composition among plant species when plants were subjected to different stresses. Mass spectrometry analysis provided evidence that oxophytodienoic acid, an oxidized fatty acid, is significantly more concentrated on the galactosyl ring of monogalactosyldiacylglycerol than on the glycerol backbone. A mass spectrometry method, measuring 272 lipid analytes with high precision in a relatively short time, was developed. Application of the method to plants subjected to wounding and freezing stress in large-scale experiments showed the method produces data suitable for lipid co-occurrence analysis, which identifies groups of lipid analytes produced by identical or inter-twined enzymatic pathways. The mass spectrometry method and lipid co-occurrence analysis were utilized to study the nature of lipid modifications and the roles of lipoxygenases and patatin-like acyl hydrolases in Arabidopsis during cold acclimation, freezing, and thawing.
Keywords: Mass spectrometry; Lipidomics; Membrane lipids; Arabidopsis thaliana; Freezing; Wounding; Biochemistry (0487); Plant Biology (0309); Systematic biology (0423)